Emotional Incest in Group Psychotherapy: A Conspiracy of Silence - Pepper, Robert S. (Rowman & Littlefield Publishers, 2014)
Emotional Incest in Group Psychotherapy: A Conspiracy of Silence is unique in the field of analytic group psychotherapy. Many books assume that the frame of therapy, the boundary between what is and isn’t therapy, is a given. This book treats the frame as a variable, showing that alterations to the frame have consequences. A moral dilemma exists when leaders choose to operate outside the ethics and wisdom of the field. The spoken directive to "say everything" is obviated by the unspoken directive not to, and hence a conspiracy of silence is created. There is potential for iatrogenic treatment reactions, constituting an abuse of power. There are at least seven dangers of blurring the boundary between therapy and not therapy: 1. Breaches of confidentiality; 2. Looping; 3. The pass along effect; 4. Gaslighting; 5. Overstimulation; 6. ‘The emperor’s new clothes’ effect; and 7. Scapegoating. Emotional Incest in Group Psychotherapy illustrates the need to avoid these seven dangers and effectively help therapists work within the group setting. Professional organizations that provide the opportunity for members to openly address their concerns about blurred boundaries in group treatment can help to mitigate their negative effects.